Fine needle aspiration in the treatment of adnexal cysts in women in menopausal period - Jędrzejczyk, Sławomir; Stachowiak, Grzegorz; Zając, Agnieszka; Krawczyk, Tomasz; Grab, Marzena; Seraficka, Agnieszka; Izdebski, Bartosz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
In this article the authors share their own experience in the field of ultrasound-guided fine needle aspiration (FNA) of simple adnexal cysts in women in the menopausal period. FNA appears to be an effective and simple healing method of these lesions, with a low recurrence incidence rate (<25%). The proper patients” qualification is extremely important in order to gain a complete recovery with the minimal oncological risk. For every case of FNA (except for cytological examination) a bacteriological evaluation of the punctate is necessary because various bacteria are often cultured and the results of microbiological (and cytological) examination of the fluid are weakly correlated with coexisting clinical signs of the patients.